Effects of fungal cell wall polysaccharides and lipopolysaccharide on in vitro tumour necrosis factor alpha production by peripheral blood mononuclear cells of sarcoidosis patients - Stopinsek, Sanjaber; Tercelj, Marjeta; Salobir, Barbara; Wra, Branka; Ihan, Alojz; Rylander, Regnar; Simcic, Sasa (Zdravniški vestnik (Ljubljana, Slovenia : 1992), 2010)
Background: Living in damp and moldy environments is being associated with a high risk for sarcoidosis and recently fungi have been suspected to be involved in the immunopathogenesis of sarcoidosis. We developed a model to study the influence of fungal cell wall polysaccharides on in vitro cytokine production by peripheral blood mononuclear cells (PBMC). We investigated whether different fungal cell wall polysaccharides induce different levels of tumour necrosis factor alpha (TNF-α) production by PBMC. We also assessed whether fungal cell wall polysaccharides modulate the lipopolysaccharide (LPS)- induced the TNF-α production by PBMC. And finally, we assessed whether there is a possible difference in TNF-α response of PBMC between patients with sarcoidosis and healthy persons. Methods: Eleven patients with newly diagnosed sarcoidosis and eleven healthy volunteers were included in the study. PBMC were isolated from whole blood and stimulated with fungal cell wall polysaccharides (soluble and particulate (1->3)-β-glucan, zymosan A and chitin) and LPS. The secretion of TNF-α was measured from cultured PBMC. Results: Particulate (1->3)-β-glucan was a potent inducer of TNF-α secretion by PBMC from patients with sarcoidosis and healthy persons. Soluble (1->3)-β-glucan, zymosan A and chitin were weak inducers of TNF-α secretion by PBMC from patients with sarcoidosis and healthy persons. Soluble (1->3)-β-glucan increased, while particulate (1->3)-β-glucan and chitin depressed the LPS induced secretion of TNF-α by PBMC from patients with sarcoidosis and healthy persons. There was no significant difference between patients with sarcoidosis and healthy persons, although there was a slight decrease of TNF-α secretion by PBMC from patients with sarcoidosis, compared to healthy persons. Conclusions: In this article we present the results of our preliminary study. We found that different fungal cell wall polysaccharides induced different levels of TNF-α production by PBMC from patients with sarcoidosis and healthy persons. Moreover, we found that some fungal cell wall polysaccharides modulated the LPS induced TNF-α secretion by PBMC from patients with sarcoidosis and healthy persons. But we found no significant deference between patients with sarcoidosis and healthy persons, although there was a slight decrease in TNF-α secretion by PBMC from patients with sarcoidosis, compared to healthy persons. The results of our study could suggest that exposure to fungi might influence the inflammatory response of the lung.